Environmental Education in Forming Attitudes ofEnvironmental Care for Students - Istiqomah, Istiqomah; Suwondo, Suwondo; L.N Firdaus, L.N Firdaus (FKIP-Universitas Riau, 2020)
Current environmental problems have become a serious threat to human life. One way to reduce this threat is to change the paradigm of the younger generation through education. Environmental Education (PLH) is the right step to implement, especially in Adiwiyata schools. This study aims to analyze students environmental care attitudes by learning monolithic and integrated environmental education. This research was conducted in 4 adiwiyata high schools. The method used is a survey. The total sample was307 students. The technique used through the questionnaire environmental attitudes of students. Data analysis was performed by t-test. The t-test results showed that therewere differences in students' environmental care attitudes between monolithic learning and integration. Differences in attitudes to care for the environment are found in 3 indicators namely, attitudes towards energy, attitudes towards flora and fauna and attitudes towards the social and human environment. Analysis of environmental care attitudes category found that monolithic PLH learning was1.24% in the excellent category, 98.76 in the goodcategory. While PLH integration is 1.39% very good,93.10% is good and 5.51% is low. It was concluded that students with monolithic PLH learning had environmental care attitudes that were better than students' attitudes withPLH integration learning.